KAJIAN HUKUM TERKAIT PENYELESAIAN NON-LITIGASI PADA PERJANJIAN PENANAMAN MODAL - Cahyaningtyas, Kartika; Witono, A.Tigor (LPPM institut Teknologi Bisnis AAS Indonesia, 2023)
This research examines and analyzes investment agreements that have not fulfilled the elements of legal requirements for agreements that apply in Indonesia legally. This is necessary because of business developments where the role of investors is very important and can expand business and partners while establishing working relationships, so the parties have more confidence in making an agreement. This agreement has also been recognized in Indonesia, so legally it has strong legal force. The method used is normative research with a problem approach, namely the case approach. The research results in the form of Investment Agreements made and implemented do not fulfill the elements in making agreements which according to the Indonesian State are recognized as legal. This causes the agreement to be null and void, but the parties to the agreement have made achievements in the form of providing capital in the form of money. This causes losses to be experienced, so that legal action is taken in a non-litigation manner (outside of court). This effort was chosen because having an agreement obtained by the parties is a win-win solution. Keywords: Investment Agreement, Legality, Non-litigation, Win-win solution